Model of Cooperative Business Competitiveness Based on Business Type in Hammer City - Syamsul Bahri Dg. Parani; Syamsuddin (Jurnal Multidisiplin Madani, 2023)
Advances in science and technology in the current century have changed the face of the world in various aspects of life, especially in the economic field. Where the economic world order becomes centered on individual profits, namely the owners of capital (capitalism). So that an economic system is needed that does not only enrich the owners of capital. One of the economic systems that can be applied to overcome this gap is the people's economy or known as cooperatives. Cooperatives that are expected by the constitution as a people's economic movement known as the pillars of the national economy have not been able to keep up with the efforts of other economic actors, due to internal and external factors, which have an impact on weak business competitiveness. Therefore, the purpose of this research is to find out and analyze how the competitiveness model of savings and loan cooperatives, services, consumers, and producers in Palu City. The analysis technique used is descriptive SWOT technique combined with generic strategies and the 2020 policy of the Indonesian Ministry of Cooperatives and SMEs on cooperative empowerment. The results obtained competitiveness strategies used by each cooperative are: savings and loan cooperatives use aggressive strategies, service cooperatives use defensive strategies, consumer cooperatives use turn-around strategies, and producer cooperatives use diversification strategies